OPTIMIZING EMPLOYEE PERFORMANCE THROUGH WORKLOAD MANAGEMENT AND WORK-LIFE BALANCE IN THE ERA OF DIGITAL COMPETITION - Tri Priyanto; Deden Sutisna (Journal of Economic, Bussines and Accounting (COSTING), 2025)
This study aims to analyze the influence of workload and work-life balance on employee performance, both partially and simultaneously, at PT Media Merdeka Network Semarang. The background of the study is based on the decline in company performance indicated by the trend of declining revenue and employee complaints about the high workload and imbalance between work and personal life. The method used is a quantitative approach with descriptive and verification techniques. Data were collected through distributing questionnaires to 88 respondents and analyzed using multiple linear regression, t-test, F-test, and multicollinearity test. The results of the analysis show that workload has a positive and significant influence on employee performance (coefficient value 0.550; sig. <0.05), as well as work-life balance which also has a positive and significant influence (coefficient value 0.493; sig. <0.05). Simultaneously, these two variables explain the variability of employee performance by 96.3% (R² = 0.963). This indicates that proportional workload management and effective implementation of work-life balance are crucial factors in improving employee productivity and performance. The implications of this research point to the need for adaptive managerial policies, including fair workload management, flexible working hours, employee welfare support, and the development of an objective and comprehensive performance evaluation system.